The role of character traits in economic games. (1st April 2017) - Ruch, Willibald; Bruntsch, Richard; Wagner, Lisa
Abstract: Notwithstanding the fact that valuing personality descriptors from the realm of character were deliberately excluded from the Big Five model of personality, in the study of economic games (EGs; e.g., the prisoner's dilemma ) the Big Five were used when predicting outcomes in the field of behaviors that are socially valued in terms of fairness and altruism (i.e., the moral domain). Eventually evaluative traits were introduced and found useful in the study of EGs, namely the HEXACO dimension honesty/humility (H/H). As an extensive list of evaluative traits, the Values In Action classification of character strengths may complement H/H when assessing character and predicting individuals' decisions in EGs. For this study, N  = 155 participants completed the Values in Action Inventory of Strengths, a measure of the HEXACO traits, and four different EGs that involved decisions relevant to fairness and altruism. Along with H/H, individuals' positions on a dimension abstracting heart-related vs. mind-related character strengths predicted outcomes in the EGs. These results support earlier findings that evaluative traits predict decisions relevant to fairness and altruism. Furthermore, character strengths can be seen as complementing H/H when predicting behavior in the moral domain by character. Highlights: There is interindividual variance in decision tendencies in economic games. Honesty/humility (H/H) predicts fair and altruistic decisions in economic games. Character strengths complement H/H as evaluative traits. Character strengths explain incremental variance in economic games above H/H. Evaluative traits are useful for predicting behavior in the moral domain.